THE TRAINING TECHNOLOGIES USE FOR TEENAGERS IN A RECREATIONAL AND DEVELOPMENTAL ENVIRONMENT - СВАТЕНКОВ, Олександр; СВАТЕНКОВА, Тетяна (Видавничо-поліграфічний центр “Київський університет”, 2024)
Background. The article examines the training technologies use peculiarities in a temporary group in the children's camp recreational and developmental environment and their role in the adolescents' psychological potential development and actualization.Methods. The test "Detecting sociometric status (method of J. Moreno) and the test of emotional intelligence (N. Hall) results are presented.Results. The basis of training technologies is the constructive interaction between a practical psychologist and teenagers' group, which combines competence and transformational approaches. The author's program concept for the adolescents' psychological potential development (authors: T.I. Svatenkova and O.V. Svatenkov) is revealed and the longitudinal study results dedicated to the training technologies implementation in a temporary children's group in a children's camp are highlighted. The personality development in a temporary children's group concept using training technologies in the children's camp recreational and developmental environment conditions, it takes into account the psychosocial, culturalintellectual and neurophysiological aspects of the recreational and leisure process, combining an individual approach to the individual. The recreational and development environment's potential study was conducted in 2017–2022. A comprehensive psychological diagnosis was carried out with children during this period, a training program for the adolescents' psychological potential activation and development was planned, developed and implemented. Combining the recreational and developmental period of the teenagers' stay in the camp with training classes, accordingly coordinated in purpose's terms, tasks and functions, a person-oriented competence approach to working with children and the transformational interaction concept, already at the first stage certain changes in behavior became noticeable, which proved long-term research of sociometric status and emotional intelligence.Conclusions. The study results show the effectiveness of using training technologies with teenagers in the recreational and developmental environment conditions, which is recorded by changes in the teenager' sociometric status and the emotional intelligence development.

Вступ. Розкрито особливості використання тренінгових технологій у рекреаційно-розвивальному середовищі для розвитку психологічного потенціалу підлітків. Висвітлено концепт авторської програми розвитку психологічного потенціалу.Методи. За 2017–2022 роки дослідженням було охоплено 2022 дитини на засадах добровільності та анонімності. Діагностичний інструментарій складається із таких методик: соціометричне опитування (Дж. Морено); діагностика "емоційного інтелекту" (Н. Холл).Результати. Результати дослідження за тестом соціометричного статусу та тестом емоційного інтелекту показують ефективність застосування тренінгових технологій в умовах рекреаційно-розвивального середовища, що фіксується змінами соціометричного статусу підлітка і розвитком емоційного інтелекту.Висновки. Використання тренінгових технологій з опорою на компетентнісний підхід створює умови, за яких позиція старшого наставника гуманна і ґрунтується на захисті прав дитини та мотивує підлітків до саморозвитку.
ВИКОРИСТАННЯ ТРЕНІНГОВИХ ТЕХНОЛОГІЙ ДЛЯ ПІДЛІТКІВ В УМОВАХ РЕКРЕАЦІЙНО-РОЗВИВАЛЬНОГО СЕРЕДОВИЩА
Keywords: підлітки; психологічний потенціал; рекреаційно-розвивальне середовище; тимчасова група; трансформаційна взаємодія; тренінг; psychological potential; recreational and developmental environment; teenagers; temporary group; training; transformational interaction